A History of the American Civil Rights Movement Through Newspaper Coverage The Race Agenda, Volume 1 - Hallock, Steve (2018)
From the cardinal Brown v. Board of Education Supreme Court ruling that desegregated U.S. public education to the demonstrations, marches, and violence of the civil rights movement, A History of the American Civil Rights Movement Through Newspaper Coverage: The Race Agenda, Volume 1 traces the crusade for justice through the lens of major newspaper coverage to reveal the combating sectional press attitudes of the era. The book details attempts, blatant and subtle, to frame the major events of the movement in themes that have resonated from before, during, and since the Civil War. States' rights versus constitutional guarantees of freedom and equality, nullification versus federal authority, and regional social and cultural mores that buttressed the prejudices and political arguments of segregation and desegregation across the nation are some of the issues covered. This analysis of the press coverage of events and issues of that tumultuous period of U.S. history-by newspapers in the North, South, Midwest, and West-exposes perspectives and press routines that remain ingrained and thus relevant today, when journalistic treatment of political debate, ranging from traditional newspapers and broadcast platforms to those of cable, social media, and the Internet, continues to set an often volatile and oppositional political agenda.